Methodology of Lease Capitalization. - Garrison, Ray H. (The Accounting Review, 1968)
Abstract Opinion No. 5 of the Accounting Principles Board is of recent enough date that accounting texts have not yet included methodology of lease capitalization as part of their content. Yet the author has found in both auditing and theory courses that discussion of methodology through development of a brief example greatly aids students in visualizing the impact of the capitalization decision on financial statements, and thereby enhances their ability to perceive and discuss underlying theoretical issues. In the article the author has developed an example as an aid to classroom discussion. Most students grasp concepts involved in the example very quickly. As the example is developed, parallels can be drawn between capitalized lease accounting and conventional methods of accounting for purchases of assets through debt financing. With these data before the student, it is a relatively easy matter to guide the class into a discussion of underlying theoretical questions and issues relating to lease financing and its impact on accounting technique.